Research on the integration of chinese excellent traditional culture and moral education in colleges and universities - Du Xingdong; Huat, Khor Teik (Journal of Islamic, Social, Economics and Development, 2024)
This paper aims to explore how to integrate Chinese excellent traditional culture with moral education. First, the excellent Chinese traditional culture is defined and its important value in moral education is explained clear. Then, the problems existing in the integration of Chinese excellent traditional culture and moral education are analyzed, including the lack of introduction of excellent traditional culture in textbooks and campus environments. In view of these problems, this paper puts forward the corresponding practical strategies, including strengthening the construction of the main channel of moral education for college students and carrying out campus cultural activities, so as to promote the integration of Chinese excellent traditional culture with moral education. Based on these strategies, we hope to further play the educational role of Chinese excellent traditional culture and improve the effectiveness of moral education for college students.